New type of magnetic structure in the R2T2X group: Tb2Pd2In. (22nd May 2020) - Maskova-Cerna, Silvie; Klicpera, Milan; Svoboda, Pavel; Andreev, Alexander V; Skourski, Yurii; Reehuis, Manfred; Hoffmann, Jens-Uwe; André, Gilles; Havela, Ladislav
Abstract: Anisotropy of bulk magnetic properties and magnetic structure studies of a Tb2 Pd2 In single crystal by means of bulk magnetization methods and neutron diffraction techniques confirmed the antiferromagnetic order below the Néel temperature 29.5 K. The collinear magnetic structure of Tb magnetic moments aligned along the tetragonal c -axis is characterized by a propagation vector k = (1/4, 1/4, 1/2), yielding an equal-moment structure with alternating coupling between nearest as well as next-nearest Tb neighbors within the basal plane and antiferromagnetic coupling between the c -axis neighbors. In the context of magnetism of R2 T2 X compounds, where R stands for rare-earth or actinide element, such collinear structure with long-wavelength periodicity represents a new type of magnetic structure.